Pengaruh Stress Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja - Ananta, Putu; Taufan, Sonny (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Human resource management is the key to company excellence. Employees who are satisfied and free from stress contribute to good performance. Factors such as motivation, rewards and career development also influence performance. PT. Tunas Mobilindo Perkasa-Tunas Daihatsu Pondok Gede is a company operating in the automotive industry by providing 3S activities in the form of vehicle unit sales, spare parts sales and service services. PT. Tunas Daihatsu Pondok Gede, an automotive company in Indonesia, measures the success of its service through vehicle unit service targets. Their sales data for 2021-2022 can provide an idea of the company’s performance. PT Tunas Mobilindo Perkasa-Tunas Daihatsu Pondok Gede is experiencing problems in achieving monthly targets related to service department employee satisfaction in 2021-2022, this problem is also caused by employee performance based on the company’s KPI values. Therefore, this research aims to determine the effect of work stress on employee performance through job satisfaction. In this research, we use the variables Job Stress (X), employee performance (Y), and job satisfaction (Z). The method used in this research is an analysis technique using Path Analysis assisted by the IBM SPSS version 25 application. The results of the research show that work stress directly has a significant influence on employee performance, this can be seen from t-count > t-table. The results of this research show that work stress indirectly has an influence on employee performance through job satisfaction. This can be seen from the path coefficient results showing that the indirect influence value is greater than the direct influence.